REDUCING SERIOUS HARM FOR PEDIATRIC CARDIAC INPATIENTS AT A LARGE CHILDREN'S HOSPITAL. Issue 11 (22nd October 2015) - Cooper, David; Storey, Jean; Mustin, Laurie; Anderson, Jeffrey; Hanke, Sam; Clarke-Meyers, Katie; Brown, James; Simon, Katie; Kimball, Thomas
Abstract : Background: Serious harm is a composite outcome that includes the following 10 preventable patient morbidities: Catheter-Associated Blood Stream Infection (CA-BSI), Catheter-Associated Urinary Tract Infection (CA-UTI), Ventilator Associated Pneumonia (VAP), Pressure Ulcer, Serious PIV extravasation, Level 6–9 Adverse Drug Events, Surgical Site Infection (SSI), Serious Falls, Preventable Codes Outside ICU, and Surgical Sentinel Events. Failure to prevent harm results in increased length of stay, cost and mortality. Objectives: In efforts to improve system level safety outcomes for cardiac patients, the Heart Institute Safety, Quality and Value leadership aligned strategic priorities and projects across our microsystems to reduce serious harm. Methods: Pareto charts identified the largest contributors to serious harm in the Heart Institute. Active QI work was then prioritized to these areas with focused QI consultant and data support. PDSA cycles were then used to test and implement change. Process control charts were used to evaluate change in the Serious Harm rate. Results: The largest contributors to harm were identified as CA-BSI, SSI and VAP. For FY15, we were able to reduce Serious Harm from 22.8 to 20.5 per 10, 000 patient days and the Centerline was shifted from 30.0 to 18.1 per 10, 000 patient days. Conclusions: Having leadership take a system level approach to drive and support alignment of QI projects resulted in reduction of Serious Harm to cardiac patients. This can be spread to other HI programs to achieve similar results.Figure 1 Figure 2